The Effect of Financial Knowledge and Subjective Norm on Shopee Paylater Use Intention with Perceived Trust as Mediator - Al-Kairana Mazaya. A; Achmad Kautsar; Anita Safitri; Dhiyan Septa Wihara (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The rapid growth of digital financial services and the increasing popularity of buy now, pay later platforms have transformed consumer payment behavior, particularly among younger generations who are highly engaged with digital technology, This study examined the determinants of intention to use Shopee PayLater among female Generation Z university students in Surabaya by integrating financial knowledge and subjective norm within the Theory of Planned Behavior, with perceived trust as a mediating variable. Using a quantitative explanatory approach, data were collected through an online questionnaire from 150 respondents and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected in 2025. The results revealed that financial knowledge did not have a direct effect on intention to use but significantly influenced perceived trust. Subjective norm showed a strong and significant direct effect on intention to use, while perceived trust significantly mediated the relationship between financial knowledge and intention to use. These findings highlight the dominant role of social influence and trust in shaping paylater adoption and imply that enhancing transparency and trust-building strategies is more critical than financial literacy alone for encouraging responsible use among Generation Z consumers.